Note: The Underage, the “Unborn,” and the Unconstitutional: An Analysis of the Child Custody Protection Act - Liebman, Joanna S. (Columbia Journal of Gender and Law, 2002)
The Child Custody Protection Act (CCPA), 2001 H.R. 476, is currently pending in the House of Representatives. The Act would impose criminal penalties on any non-parent adult who transports a minor across state lines to receive an abortion, if that minor has not satisfied the parental consent or notification laws in her home state. The Bill reads: Except as provided in subsection (B), whoever knowingly transports an individual who has not attained the age of 18 years across a state line, with the intent that such individual obtain an abortion, and thereby in fact abridges the right of a parent under a law requiring parental involvement in a minor’s abortion decision, in force in the state where the individual resides, shall be fined under this title or imprisoned not more than one year, or both. Purportedly, this Bill would deter rapists and child molesters from forcing abortions on their kidnapped victims. However, it would have the very real effect of preventing teenagers from seeking help, even from other family members. In fact, proponents of the Bill rejected an amendment that would have excluded grandparents from criminal sanctions. One might take several approaches in assessing the constitutionality of the CCPA; an initial instinct is to challenge the law under the “undue burden” standard articulated by the Supreme Court in Planned Parenthood of Southeastern Pennsylvania v. Casey. Reliance on Casey would be misplaced, however, since the Court in that case specifically found that parental notification or consent laws themselves do not place an undue burden on a minor. If laws requiring a minor to secure parental consent do not constitute an undue burden, it is extremely unlikely that the Court would find the minor’s inability to be taken out of state in circumvention of those laws to compose one either.